Effect of pyrolyzed catecholamine polymers for concurrent enhancements of electrical conductivity and mechanical strength of graphene-based fibers. (20th October 2019) - Kim, Joonhui; Hwang, Hoseong; Chan Yoo, Sung; Seo, Hojin; Ryu, Seongwoo; Hong, Soon Hyung
Abstract: Graphene fibers are regarded as a novel platform material for flexible electronic applications based on their superior electrical conductivity, mechanical properties and potential for mass production. However, properties of graphene fibers are still far from commercial level and considerable effort has been made recently to improve these characteristics. In this paper, we drastically enhanced both the mechanical and electrical properties of graphene-based fibers by converting infiltrated polydopamine (PDA) into N-doped graphitic layers. Graphene-based fibers were fabricated from a liquid crystalline graphene oxide dispersion, and PDA was introduced into the fibers. After pyrolysis, the mechanical properties, i.e., the tensile strength and Young's modulus, of the composite graphene-based fibers exhibited 3.56- and 3.95-fold increases, respectively, compared with those of pristine graphene fibers. Furthermore, the electrical conductivity also dramatically increased to 7.3 × 10 4  S/m, which is almost 10 times that of pristine graphene fibers. These results show the achievement of advantages superior to those in previously reported studies based on polymer-grafted graphene composite fibers. This hybridized composite fabrication process provides a new way of reinforcing graphene fibers and contributes to expanding the application of graphene-based fibers in flexible electronic devices.